Yarrowia lipolytica as an Oleaginous Platform for the Production of Value-Added Fatty Acid-Based Bioproducts - Liu, Huhu; Song, Yulan; Fan, Xiao; Wang, Chong; Lu, Xiangyang; Tian, Yun (Frontiers in Microbiology, 2021)
The microbial fermentation process has been used as an alternative pathway to the production of value-added natural products. Of the microorganisms, Yarrowia lipolytica, as an oleaginous platform, is able to produce fatty acid-derived biofuels and biochemicals. Nowdays, there are growing progresses on the production of value-added fatty acid-based bioproducts in Y. lipolytica. However, there is less review performing the metabolic engineering strategies and summarizing the current production of fatty acid-based bioproducts in Y. lipolytica. To this end, we briefly provide the fatty acid metabolism, including fatty acid biosynthesis, transportation and degradation. Then, we introduce the various metabolic engineering strategies for increasing bioproducts accumulation in Y. lipolytica. Further, the advanced progress in the production of fatty acid-based bioproducts by Y. lipolytica, including nutraceuticals, biofuels and biochemcials, is summarized. This review will provide attractive thoughts for researchers worked on the field of Y. lipolytica.